An intriguing Z-scheme titania loaded on fibrous silica ceria for accelerated visible-light-driven photocatalytic degradation of ciprofloxacin - Anees Ameera, Fauzi; Aishah, Abdul Jalil; Nurul Sahida, Hassan; F. F.A., Aziz; M. S., Azami; Tuan Amran, Tuan Abdullah; Mohd Fadhzir, Ahmad Kamaroddin; Herma Dina, Setiabudi (Academic Press Inc., 2022)
A novel Z-scheme titania loaded on fibrous silica ceria (Ti-FSC) was triumphantly fabricated via hydrothermal followed by electrolysis method and evaluated for the visible-light degradation of ciprofloxacin (CIP). Noticeably, Ti-FSC exhibits as an efficient photocatalyst for CIP photodegradation with 95% as followed by titania loaded on fibrous silica (Ti-FS) (68%), Ti–CeO2 (35%), FSC (47%), FS (22%), and CeO2 (17%). The combination of the inherent merits of Ti loaded on FSC is able to realize the crucial role of Ce in harnessing the high dispersion of Ti, which could beneficial for improving the performance proven by XRD, FESEM, TEM and FTIR. Consequently, high dispersion of Ti on FSC has worthwhile towards the interaction of the Si–O–Ti, Ce–O–Ti, and Si–O–Ti, which could enhance the CIP photodegradation by providing more surface defects, narrowing the band gap, improving electron-hole separation and suppressing electron-hole recombination that revealed by XPS, UV–vis/DRS, Nyquist plots and PL studies, respectively. The scavenger study revealed that the controlling species in the system was hydroxyl radical and holes. A potential Z-scheme heterojunction mechanism for Ti-FSC was deduced from the band structure analysis. The possible photodegradation pathway was proposed based on GCMS analysis. Besides, the acceptable reusability, which exceeded 90% of degradation indicated the great application potential of Z-scheme Ti-FSC in wastewater treatment and others application.